2016
DOI: 10.1177/1740774516673362
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian survival analysis in clinical trials: What methods are used in practice?

Abstract: Background: Bayesian statistics are an appealing alternative to the traditional frequentist approach to designing, analysing, and reporting of clinical trials, especially in rare diseases. Time-to-event endpoints are widely used in many medical fields. There are additional complexities to designing Bayesian survival trials which arise from the need to specify a model for the survival distribution. The objective of this article was to critically review the use and reporting of Bayesian methods in survival trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Brard et al [245] found evidence of poor reporting of Bayesian methods. To address this, when a Bayesian AD is used, authors should detail the model used for analysis to estimate the posterior probability distribution; the prior distribution used and rationale for its choice; whether the prior was updated in light of interim data and how; and clarify the stages when the prior information was used (interim or/and final analysis).…”
Section: Section 12 Statistical Methodsmentioning
confidence: 99%
“…Brard et al [245] found evidence of poor reporting of Bayesian methods. To address this, when a Bayesian AD is used, authors should detail the model used for analysis to estimate the posterior probability distribution; the prior distribution used and rationale for its choice; whether the prior was updated in light of interim data and how; and clarify the stages when the prior information was used (interim or/and final analysis).…”
Section: Section 12 Statistical Methodsmentioning
confidence: 99%
“…Half of the studies were of diseases described as rare. 171 Only one of the 28 applications elicited priors from experts. 172 3.…”
Section: Identification Of Examplesmentioning
confidence: 99%
“…While a rich array of Bayesian methods for incorporating historical data exist, these approaches are still rarely implemented in practice. A systematic review of clinical trials published before September 2015 identified only 28 trials using Bayesian methods to analyse a censored endpoint, and of these, only four made use of historical data to estimate the treatment effect [30]. In these trials, historical data were incorporated without being down-weighted and without survival regression models being used.…”
Section: Introductionmentioning
confidence: 99%